The Activity of Papaya Seeds (Carica papaya L.) Varieties of “Bangkok” and “California” in Inhibiting the Growth of Pathogenic Bacteria - Roszelina Abd Rahman; Hilda Awaliah; Nora Syazehan Jems (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to evaluate the antibacterial activity of ethanol extracts from Bangkok and California papaya (Carica papaya) seeds against E. coli, Salmonella sp., and S. aureus, and to identify the chemical compounds responsible for their antibacterial properties using GC–MS analysis. Methodology: This study applied a Completely Randomized Design (CRD) using ethanol extracts of Carica papaya seeds. Equipment included GC–MS, rotary evaporator, autoclave, laminar flow, vortex mixer, hot plate, incubator, and micrometer. Media and reagents were NA, NB, MHA, ethanol, DMSO, and Amoxicillin. Tested bacteria were E. coli, Salmonella sp., and S. aureus. Data were analyzed with ANOVA and DMRT using SPSS. Main Findings: Ethanol extracts of Carica papaya seeds (‘Bangkok’ and ‘California’) significantly inhibited E. coli, Salmonella sp., and S. aureus growth. The highest inhibition zones occurred at 20% concentration, with ‘California’ showing stronger activity against Salmonella sp. and ‘Bangkok’ against S. aureus. MIC was 20% for Gram-negative bacteria. GC–MS identified 20 compounds in ‘Bangkok’ and 24 in ‘California’, dominated by hexadecanoic acid and various alkaloids, flavonoids, terpenoids, and fatty acids. Novelty/Originality of this study: This study provides new insights by comparing the antibacterial activity and chemical composition of ethanol extracts from Carica papaya seeds of ‘Bangkok’ and ‘California’ varieties. It identifies specific bioactive compounds through GC–MS and reveals variety-dependent antibacterial effects, advancing knowledge of papaya seeds as natural antibacterial agents and supporting their potential development as alternative antimicrobial resources.